Who goes electric? The anatomy of electric car ownership in Norway. (March 2021) - Fevang, Elisabeth; Figenbaum, Erik; Fridstrøm, Lasse; Halse, Askill H.; Hauge, Karen E.; Johansen, Bjørn G.; Raaum, Oddbjørn
Highlights: Study of household car ownership in a mature market for electric cars. Owning electric cars increases in wealth, income and education. Owners of electric cars have become more similar to other car owners over time. Owning electric cars is related to privileges for electric cars on travel to work. Buyers of electric cars are more likely to keep old car than other new car buyers. Abstract: We describe the anatomy of electric car ownership in Norway, the country with the highest market share of low-emission vehicles, using matched administrative micro data covering the entire population of private car owners. Our results show that socioeconomic characteristics are strong predictors of the car portfolio. Battery electric vehicle (BEV) ownership is increasing in wealth, income and education. While early BEV owners differed from other car owners, over time BEV owners have become more similar to other car owners. We document a strong association between BEV privileges on the travel to work (like toll road exemptions and bus lane access) and BEV ownership. We show that BEV buyers are less likely than other car buyers to sell their old car, but this difference has diminished over time.